Relative Effects of Time-Restricted Eating, Energy-Restricted Eating, and Unrestricted Eating on Eating Patterns and Dietary Intake: Results From a Randomized Controlled Trial - Lisa J. Harnack; Niki Oldenburg; Qi Wang; Erika Helgeson; Abdisa Taddese; Nicole LaPage; Alison Alvear; Alison Wong; Michelle Hanson; Julie D. Anderson; Brad P. Yentzer; Douglas G. Mashek; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

High-resolution mapping of carbonate system parameters over coastal waters using integrated uncrewed aircraft systems (UAS) and Autonomous Surface Vessel (ASV) observations - Mohammad O. S. Chowdhury; Padmanava Dash; Abduselam M. Nur; Mohammad S. Islam; Rajendra M. Panda; Gray Turnage; Lee Hathcock; Gary D. Chesser; Robert J. Moorhead (International Journal of Remote Sensing, 2026)

Transcriptomic and Hormonal Regulation of Rice Defence Against Brown Planthopper - Guru-Pirasanna-Pandi Govindharaj; Rudramadhab Panda; Kutubuddin Molla; Romio Saha; Mridul Chakroborti; Meera Kumari Kar; C. Parameswaran; S. Raghu; B. Parameswari; S. D. Mohapatra (Journal of Crop Health, 2026)

Scope and Feasibility of Enhancing the Irrigation Potential of the Kukadi Canal Command of Maharashtra, India - R. K. Panda; U. A. Amarasinghe; A. Sarangi; A. K. Sikka; S. D. Gorantiwar; V. Mandave; S. Mahapatra (Irrigation and Drainage, 2026)
Improving water use efficiency (WUE) in canal irrigation systems is vital for increasing agricultural output and maintaining ecological sustainability. Studies carried out in the Sina and Kukadi Left Bank Canal (KLBC) networks of Maharashtra, India, revealed marked disparities in the efficiency of the economic use of irrigation water. Investigations undertaken using geospatial tools highlighted a larger water influence zone (WIZ) in these systems, a factor often overlooked in conventional irrigation management. This finding led to the possibility of increasing the WUE by 113%, land productivity by 90% and EWP by 26% in KLBC, demonstrating the potential for optimising water resources and improving crop productivity. Additionally, the adoption of climate‐resilient and water‐efficient crop varieties resulted in a potential net value of output (NVOUP) increase of 80% in the KLBC irrigation system. These results emphasised the need for a comprehensive approach to irrigation water management that incorporates a detailed assessment of WIZ, conjunctive water use and sustainable cropping patterns. Such measures will not only improve water use efficiency but also contribute to a more sustainable and economically viable agricultural landscape in canal ecosystems.

Hydrodynamic performance of H-shaped floating breakwater in the presence of a partially reflecting seawall - Aparna Panda; Ronit Muduli; D. Karmakar; Manu Rao (Marine Georesources & Geotechnology, 2026)

Identifying potent inhibitors for Mycobacterium tuberculosis MabA (FabG1) - Debashis Panda; Jitendra Maharana; Arjun Sharma; Sachin B. Wadavrao; Abhishek Chowdhury; Monjur Ahmed Laskar; Mahendra K. Modi; Manabendra D. Choudhury (Molecular Diversity, 2026)

Deciphering the Neurotoxic Burden of Micro- and Nanoplastics: From Multi-model Experimental Evidence to Therapeutic Innovation - Smita Kumari; M. Yasmin Begum; Chingakham Chinglenthoiba; Khadga Raj Aran; Siva Parsad Panda; Mosleh Mohammad Abomughaid; Sorabh Lakhanpal; D. Avinash; Niraj Kumar Jha; Rohan Gupta (Molecular Neurobiology, 2025)

Ensemble deep learning framework for groundwater storage forecasting under hydrological variability - Asit Kumar Dandapat; Prafulla Kumar Panda; Sovan Sankalp; Ozgur Kisi; Habib Kraiem; Olga D. Kucher; Aqil Tariq (Acta Geophysica, 2025)

The Ubiquitin–Proteasome System in Brain Disorders: Pathogenic Pathways, Post-Translational Tweaks, and Therapeutic Frontiers - Rohan Gupta; M Yasmin Begum; Reetesh Kumar; Jyoti Gupta; Rupak Nagraik; Siva Parsad Panda; Mosleh Mohammad Abomughaid; Sorabh Lakhanpal; Avinash D; Riyaz Ali M. Osmani; Niraj Kumar Jha (Journal of Neuroimmune Pharmacology, 2025)

Effect of seabed condition on the hydrodynamic performance of a pile-restrained H-shaped floating breakwater - Aparna Panda; D. Karmakar; Manu Rao (Marine Georesources & Geotechnology, 2025)

Seagrass conservation in a dynamic tidal creek system: Balancing creek stability and nutrient loads for sustainable management - Mukunda Kesari Khadanga; Rajani Kanta Mishra; Rabindra Kumar Sahoo; D. Prabin Dora; Anil Kumar Behera; Uma Sankar Panda; Pratap Kumar Mohanty; Pravakar Mishra (Science of The Total Environment, 2025)

Exploring the Role of Serum Lysyl Oxidase (LOX) Levels and LOX Gene Polymorphism (G473A) in Diabetic Nephropathy - D. Gayathri Devi; Manaswini Mangaraj; Sandip Kumar Panda; Suchitra Kumari; Gautom Kumar Saharia (Indian Journal of Clinical Biochemistry, 2025)

Microglial pyroptosis in neurological disorders: mechanistic crosstalk, metabolic triggers, and therapeutic frontiers - Reetesh Kumar; Siva Parsad Panda; Mosleh Mohammad Abomughaid; Sorabh Lakhanpal; D. Avinash; Niraj Kumar Jha; Rohan Gupta (Metabolic Brain Disease, 2025)

Jasmonate Responsive SlnsLTP Confers Resistance Against Botrytis cinerea and Verticillium dahliae in Tomato - Sayantan Panda; Namarta C. Singh; Prashant D. Sonawane; Sagit Meir; Avinash C. Kamble (Journal of Plant Growth Regulation, 2025)

Spatiotemporal dynamics of cyanobacterial blooms: Integrating machine learning and feature selection techniques with uncrewed aircraft systems and autonomous surface vessel data - Mohammed Shakiul Islam; Padmanava Dash; John P. Liles; Hafez Ahmad; Abduselam M. Nur; Rajendra M. Panda; Jessica S. Wolfe; Gray Turnage; Lee Hathcock; Gary D. Chesser; Robert J. Moorhead (Journal of Environmental Management, 2025)

Age and origin of the Ngankipari Formation in the Noarlunga and Willunga embayments, southern South Australia - R. P. Bourman; S. Buckman; D. K. Panda; D. Banerjee; C. V. Murray-Wallace; W. Preiss (Australian Journal of Earth Sciences, 2025)

Long-lived mantle plume for the emplacement of Paleoproterozoic Dharwar-Bastar Large Igneous Province: Geochemical and Sr Nd isotope constraints from mafic rocks of Dharwar craton, India - V. Parashuramulu; Tavheed Khan; Aurovinda Panda; D. Srinivasa Sarma (Geochemistry, 2025)

Loganic Acid Alleviates the Olfactory-Brain NLRP3 Inflammasome Activation and Rescues Dopaminergic Neurons in Experimental Models of Parkinson’s Disease - Samir Ranjan Panda; Pallabi Panja; Meenakshi Singh; Ujjawal Soni; Bishal Rajdev; Pankaj Garg; Sharad D. Pawar; Rabinarayan Acharya; Anagha Ranade; V. G.M Naidu (Journal of Neuroimmune Pharmacology, 2025)

Development of India Meteorological Department: High Resolution Rapid Refresh (IMD-HRRR) Modeling System for Very Short Range Weather Forecasting - Akhil Srivastava; Prashant Kumar; Sambit Kumar Panda; Ananda Kr. Das; D. R. Pattanaik; M. Mohapatra (Pure and Applied Geophysics, 2024)

Hydrodynamic analysis of an H-shaped pile-restrained floating breakwater combined with a pair of vertical barriers - Aparna Panda; D. Karmakar; Manu Rao (Ocean Engineering, 2024)

Development of Geopark for Protecting Karst Region of Nongkhlieh Area, Meghalaya - Dipanwita Sengupta; Som Dutt; Brian D. Kharpran Daly; Sandeep Panda (Geoheritage, 2024)

Rice-based integrated farming system improves the soil quality, bacterial community structure and system productivity under sub-humid tropical condition - Prafulla Kumar Nayak; A. K. Nayak; B. B. Panda; A. Senapati; P. Panneerselvam; A. Kumar; R. Tripathi; A. Poonam; M. Shahid; S. D. Mohapatra; Megha Kaviraj; Upendra Kumar (Environmental Geochemistry and Health, 2024)

Tsunami or storm? A high-level coastal boulder field on the southern tip of Eyre Peninsula, South Australia - R. P. Bourman; C. V. Murray-Wallace; D. Panda; S. Buckman; D. Banerjee; D. D. Ryan; L. T. White (Australian Journal of Earth Sciences, 2024)

Green synthesis of calcium oxide nanoparticles impregnated activated carbon from algal–bacterial activated sludge: its application in ciprofloxacin removal - R. K. Oruganti; D. Pal; T. K. Panda; D. Shee; D. Bhattacharyya (International Journal of Environmental Science and Technology, 2023)

Satellite Epidemic of Covid-19 Associated Mucormycosis in India: A Multi-Site Observational Study - Aanchal Satija; Tanu Anand; Aparna Mukherjee; Poonam Sharma Velamuri; Kh. Jitenkumar Singh; Madhuchhanda Das; Kripa Josten; Archana Y. Keche; Nitin M. Nagarkar; Prashant Gupta; D. Himanshu; Sejal N. Mistry; et al. (Mycopathologia, 2023)

Gloriosa simplex L. (Colchicaceae): a new distributional record for India - S. P. Panda; Titir Saha; Sattom Dasgupta; R. D. Barman; S. K. Arjun; Ravi Prasad; Devendra Singh (Vegetos, 2023)

Precise Pb-Pb baddeleyite geochronology, geochemistry, and Sr-Nd isotopic constraints on the 2.36 & 1.88 Ga mafic dykes from the Bastar craton, India: Implications for their petrogenesis in conjunction with the Dharwar mafic dykes - Aurovinda Panda; Ravi Shankar; D. Srinivasa Sarma; Rahul Patel (Precambrian Research, 2023)

Ambient particulate matter (PM2.5) exposure contributes to neurodegeneration through the microbiome-gut-brain axis: Therapeutic role of melatonin - Samir Ranjan Panda; Vishal Balu Chaudhari; Sahabuddin Ahmed; Mohit Kwatra; Aishwarya Jala; Srikanth Ponneganti; Sharad D. Pawar; Roshan M. Borkar; Pawan Sharma; V.G.M. Naidu (Environmental Toxicology and Pharmacology, 2023)

Chronology and paleoclimatic implications of the upper Ganga catchment floods since Marine Isotopic Stage-2 - Neha Chauhan; Yaspal Sundriyal; Sameeksha Kaushik; Poonam Chahal; D.K. Panda; D. Banerjee; Ambili Narayanan; A.D. Shukla (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Agronomic manipulation in main season and ratoon rice influences growth, productivity, and regeneration ability in tropical lowlands - B. Lal; Priyanka Gautam; A.K. Nayak; R. Raja; B.B. Panda; R. Tripathi; M. Shahid; D. Chatterjee; P. Bhattacharyya; P. Bihari; Teekam Singh; S.K. Meena; et al. (Field Crops Research, 2023)

HIV-1 exploits Hes-1 expression during pre-existing HPV-16 infection for cancer progression - Serena D’Souza; Arati Mane; Linata Patil; Aazam Shaikh; Madhuri Thakar; Vandana Saxena; Leila Fotooh Abadi; Sheela Godbole; Smita Kulkarni; Raman Gangakhedkar; Padma Shastry; Samiran Panda (VirusDisease, 2023)

Mild-temperature Organosolv treatment of rice-straw: extracting ability of dimethylformamide and material applications - B. B. Kanrar; S. Singh; S. K. Pal; D. Panda (International Journal of Environmental Science and Technology, 2023)

Geochemistry, magma flow characteristics and petrogenesis of Paleoproterozoic NW–NNW trending mafic dykes from central Bastar craton, India - Aurovinda Panda; D Srinivasa Sarma; Rahul Patel (Journal of Earth System Science, 2022)

Assessment of long-term impact of solar activity on the ionosphere over an African equatorial GNSS station - Mefe Moses; Sampad Kumar Panda; Joseph D. Dodo; Lazarus M. Ojigi; Kola Lawal (Earth Science Informatics, 2022)

Coupled hydrodynamic and water quality modeling in the coastal waters off Chennai, East Coast of India - Umakanta Pradhan; Uma Sankar Panda; Subrat Naik; Pravakar Mishra; D. Satish Kumar; Mehmuna Begum; M. V. Raman Murthy (Frontiers in Marine Science, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Mapping the functional brain state of a world champion freediver in static dry apnea - Jitka Annen; Rajanikant Panda; Charlotte Martial; Andrea Piarulli; Guillaume Nery; Leandro R. D. Sanz; Juan M. Valdivia-Valdivia; Didier Ledoux; Olivia Gosseries; Steven Laureys (Brain Structure and Function, 2021)

Molecular Evidence and Sequence Analysis of Goatpox Virus Isolates from Assam, India: An Emerging Viral Disease of Goats - D. P. Bora; G. Venkatesan; S. Arya; A. O. Pariat; Amit Kumar; Sabnam Ingtipi; Puja Mech; G. B. Manjunatha Reddy; Shyama P. Panda; N. N. Barman; V. Balamurugan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Geochemistry and petrogenesis of tholeiitic dykes from the Chotanagpur Gneissic Complex, eastern India - Rahul Patel; Ravi Shankar; D Srinivasa Sarma; Aurovinda Panda (Journal of Earth System Science, 2021)

Geochemistry of aerodynamically distorted Australasian microtektites: Implications for ejecta on Mars and Venus - N G Rudraswami; M Shyam Prasad; Sridhar D Iyer; M Pandey; Christoph Helo; Dipak Kumar Panda (Journal of Earth System Science, 2021)

Luminescence dating of Quaternary alluvial successions, Sellicks Creek, South Mount Lofty Ranges, southern Australia - R. P. Bourman; D. Banerjee; C. V. Murray-Wallace; S. Buckman; D. K. Panda; A. P. Belperio; C. L. Jayawardena (Australian Journal of Earth Sciences, 2020)

Prediction of upslope movement of Rhododendron arboreum in Western Himalaya - Sri N. S. Veera; Rajendra M. Panda; Mukunda D. Behera; Shailendra Goel; Partha S. Roy; Saroj K. Barik (Tropical Ecology, 2019)

Insights into the recent Kotropi landslide of August 2017, India: a geological investigation and slope stability analysis - S. P. Pradhan; S. D. Panda; A. R. Roul; M. Thakur (Landslides, 2019)

Rapid detection of Salmonella contamination in seafoods using multiplex PCR - Brundaban Sahu; Shiva D. Singh; Bijay Kumar Behera; Satyen Kumar Panda; Abhishek Das; Pranaya Kumar Parida (Brazilian Journal of Microbiology, 2019)

Quantitative Approaches in Adaptation Strategies to Cope with Increased Temperatures Following Climate Change in Potato Crop - R. K. Srivastava; Arunbabu Talla; D. K. Swain; R. K. Panda (Potato Research, 2019)

Inter-relationship between intercepted radiation and rice yield influenced by transplanting time, method, and variety - Priyanka Gautam; B. Lal; A. K. Nayak; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; U. Kumar; M. J. Baig; D. Chatterjee; C. K. Swain (International Journal of Biometeorology, 2019)

Assessing the performance of WRF model in predicting high-impact weather conditions over Central and Western Africa: an ensemble-based approach - P. Moudi Igri; Roméo S. Tanessong; D. A. Vondou; Jagabandhu Panda; Adamou Garba; F. Kamga Mkankam; A. Kamga (Natural Hazards, 2018)

First record of Metanophrys sinensis (Protozoa: Ciliophora: Scuticociliatida) from India causing large scale mortality in a new host Macrobrachium rosenbergii larvae - P K Sahoo; S Pattanayak; A Paul; M K Sahoo; P Rajesh Kumar; D Panda; B R Pillai (Journal of Fish Diseases, 2018)

Use of satellite remote sensing as a monitoring tool for land and water resources development activities in an Indian tropical site - M. D. Behera; A. K. Gupta; S. K. Barik; P. Das; R. M. Panda (Environmental Monitoring and Assessment, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

A study of 2014 record drought in India with CFSv2 model: role of water vapor transport - S. S. V. S. Ramakrishna; V. Brahmananda Rao; B. R. Srinivasa Rao; D. Hari Prasad; N. Nanaji Rao; Roshmitha Panda (Climate Dynamics, 2017)

Overexpression of HDAC9 promotes oral squamous cell carcinoma growth, regulates cell cycle progression, and inhibits apoptosis - Bhawna Rastogi; Satish K. Raut; Naresh K. Panda; Vidya Rattan; Bishan D. Radotra; Madhu Khullar (Molecular and Cellular Biochemistry, 2016)

Impairment of soil health due to fly ash-fugitive dust deposition from coal-fired thermal power plants - R. Raja; A. K. Nayak; A. K. Shukla; K. S. Rao; Priyanka Gautam; B. Lal; R. Tripathi; M. Shahid; B. B. Panda; A. Kumar; P. Bhattacharyya; G. Bardhan; et al. (Environmental Monitoring and Assessment, 2015)

Added-Value of 3DVAR Data Assimilation in the Simulation of Heavy Rainfall Events Over West and Central Africa - P. Moudi Igri; Roméo S. Tanessong; D. A. Vondou; F. Kamga Mkankam; Jagabandhu Panda (Pure and Applied Geophysics, 2015)

Analyses of rainfall using probability distribution and Markov chain models for crop planning in Daspalla region in Odisha, India - K. G. Mandal; J. Padhi; A. Kumar; S. Ghosh; D. K. Panda; R. K. Mohanty; M. Raychaudhuri (Theoretical and Applied Climatology, 2015)

Novel lead generation of an anti-tuberculosis agent active against non-replicating mycobacteria: exploring hybridization of pyrazinamide with multiple fragments - Shankar D. Markad; Parvinder Kaur; B. K. Kishore Reddy; Murugan Chinnapattu; Anandkumar Raichurkar; Radha Nandishaiah; Manoranjan Panda; Pravin S. Iyer (Medicinal Chemistry Research, 2015)

Statistical modeling to women self-help groups of Odisha based on socio-economic developmental parameters in aquaculture - Nirupama Panda; A. S. Mahapatra; D. P. Rath (Aquaculture International, 2015)

Spatio-temporal distribution of major and trace metals in estuarine sediments of Dhamra, Bay of Bengal, India—its environmental significance - D. R. Satapathy; C. R. Panda (Environmental Monitoring and Assessment, 2015)

Dispersion pattern of petroleum hydrocarbon in coastal water of Bay of Bengal along Odisha and West Bengal, India using geospatial approach - P. K. Panigrahy; D. R. Satapathy; C. R. Panda; R. N. Kar (Environmental Monitoring and Assessment, 2014)

Age and geochemistry of the Newania dolomite carbonatites, India: implications for the source of primary carbonatite magma - Jyotiranjan S. Ray; Kanchan Pande; Rajneesh Bhutani; Anil D. Shukla; Vinai K. Rai; Alok Kumar; Neeraj Awasthi; R. S. Smitha; Dipak K. Panda (Contributions to Mineralogy and Petrology, 2013)

Modelling and analyzing the watershed dynamics using Cellular Automata (CA)–Markov model – A geo-information based approach - MUKUNDA D BEHERA; SANTOSH N BORATE; SUDHINDRA N PANDA; PRITI R BEHERA; PARTHA S ROY (Journal of Earth System Science, 2012)

Studies on performance of radial solar convective sprinkler with forced evaporation - D. Lakshmanan; Rames C. Panda; G. Sekaran; M. Ramajayam; V. Arutchelvan (Clean Technologies and Environmental Policy, 2012)

Assessing Flood Induced Land-Cover Changes Using Remote Sensing and Fuzzy Approach in Eastern Gujarat (India) - Chandra S. Sharma; Mukund D. Behera; Atmaram Mishra; Sudhindra N. Panda (Water Resources Management, 2011)

Impact of bottom trawling on sediment characteristics—a study along inshore waters off Veraval coast, India - Usha Bhagirathan; B. Meenakumari; K. V. Jayalakshmy; S. K. Panda; V. R. Madhu; D. T. Vaghela (Environmental Monitoring and Assessment, 2010)

Genetics of resistance to Cucumber mosaic virus in Cucumis sativus var. hardwickii R. Alef - A. D. Munshi; Bishwajit Panda; Bikash Mandal; I. S. Bisht; E. S. Rao; Ravinder Kumar (Euphytica, 2008)

Satellite detection of earthquake thermal infrared precursors in Iran - Arun K. Saraf; Vineeta Rawat; Priyanka Banerjee; Swapnamita Choudhury; Santosh K. Panda; Sudipta Dasgupta; J. D. Das (Natural Hazards, 2008)

Analysis of water and food security scenarios for 2025 with the PODIUM model: the case of Agro‐Ecological Region 12 of India - R. B. Singandhupe; P. Nanda; D. K. Panda; M. Swain (Irrigation and Drainage, 2008)
The Policy Interactive Dialogue Model (PODIUM), developed by the International Water Management Institute (IWMI), has been used to consider data of 1995 as a base to predict water–food security scenarios for 2025 of Agro‐Ecological Region 12 (AER12) of India having a total geographical area of 26.8 million ha. The model has been used to address the food and water security issues simultaneously and generates alternative scenarios highlighting the interlinkages between water and food security. In this study four scenarios: business as usual scenario (BAU); food security scenario (FS); water security scenario (WS); and water and food security scenario (WFS) have been analysed. The BAU scenario projects that the region AER12 of India will face a food deficit of 7.46 million t in 2025. The total annually renewable water resources of the region will be 40.3 billion m 3 in 2025, out of which a maximum of 21.7 billion m 3 will be available in Agro‐Ecological Sub Region (AESR12.1), followed by 10.2 and 8.3 billion m 3 in AESR12.2 and AESR12.3, respectively. The diversion of available water in all sectors (agriculture, domestic, industry) in AER12 was 15.4 billion m 3 in 1995, which is expected to increase by 81.7% in 2025, but due to urbanisation and industrial demand, the available water for the agricultural sector is expected to reduce by 64%. In the industry sector it is projected to jump from 10% in 1995 to 28% in 2025. After analysing the BAU scenario of the region, some of the specific alternative options have been explored with the PODIUM model by altering the drivers in order to find feasible ways to make the region secure and sustainable with a comfortable level of food and water by 2025. The outcomes of the alternative options are discussed in this paper. Copyright © 2008 John Wiley & Sons, Ltd.

MODIS land surface temperature data detects thermal anomaly preceding 8 October 2005 Kashmir earthquake - S. K. Panda; S. Choudhury; A. K. Saraf; J. D. Das (International Journal of Remote Sensing, 2007)

Satellite data in a rapid analysis of Kashmir earthquake (October 2005) triggered landslide pattern and river water turbidity in and around the epicentral region - J. D. Das; A. K. Saraf; S. Panda (International Journal of Remote Sensing, 2007)

Optimal Crop Planning and Conjunctive Use of Water Resources in a Coastal River Basin - Laxmi Narayan Sethi; D. Nagesh Kumar; Sudhindra Nath Panda; Bimal Chandra Mal (Water Resources Management, 2002)